2014
DOI: 10.4137/cmc.s15230
|View full text |Cite
|
Sign up to set email alerts
|

Transpopliteal Balloon-Assisted Excimer–Laser Atherectomy for the Treatment of Chronic Femoropopliteal Occlusions: Feasibility and Initial Results

Abstract: PURPOSERecanalization of chronic total occlusions (CTOs) of the femoropopliteal arteries depends on a successful lesion crossing with the guide wire. The aim of this retrospective study was to evaluate the safety, feasibility, and the primary results of retrograde recanalization of CTOs with balloon-assisted excimer–laser atherectomy (ELA) via a transpopliteal approach after failed antegrade attempts.METHODSA total number of 15 patients (10 male, 5 female) with a mean age of 68.5 years (range: 43–91 years) tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
0
1
1
Order By: Relevance
“…There were no major adverse events regarding the laser atherectomy or popliteal access site. Compared with the results reported by Lüdtke et al (42), 7 patients of the present study required a retrograde recanalization access (including distal SFA/popliteal artery P1 segment, posterior tibial artery and peroneal artery). The technical success rate was 100%.…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…There were no major adverse events regarding the laser atherectomy or popliteal access site. Compared with the results reported by Lüdtke et al (42), 7 patients of the present study required a retrograde recanalization access (including distal SFA/popliteal artery P1 segment, posterior tibial artery and peroneal artery). The technical success rate was 100%.…”
Section: Discussioncontrasting
confidence: 66%
“…Lüdtke et al (42) reported that 15 patients (15/67, 22%) who underwent ELA-assisted PTA of the femoropopliteal arteries were treated via a retrograde transpopliteal approach. Technically successful recanalization was achieved in 14 of the 15 patients.…”
Section: Discussionmentioning
confidence: 99%